Assessment of climate change impacts on agriculture in Mali (International Journal of Scientific Research and Management (IJSRM), 2021)
This study examined the total, direct and indirect effects of climatic variables (temperature and precipitation) on crop yields (maize and millet) between regions located in close proximity to each other a spatial panel analysis of five administrative regions of Mali over a period of 30 years (1988-2017). Our results show that temperature and rainfall have direct, indirect and total effects on maize yield, while the direct effect on millet yield is not statistically significant. In other words, the effect on regions closely linked to region i where the change in temperature or rainfall occurred will be greater than the effect on more remote regions. In addition, the coefficient of variation of precipitation and the interaction between temperature and precipitation as well as area planted all have negative impacts on maize yield. However, millet yield is negatively correlated with drought in the study area. Based on these findings, decision-makers need to take into account that conditions in surrounding areas can influence cereal crop yields and that spillover effects differ between crop types. Investments in agricultural research and development must be encouraged to counter the effects of climate change.